VIIe exposition internationale de gravure. - Krzisnik, Zoran; Biennale Ljubljana 1967 (Ljubljana : Moderna Galerija, 1967)
Abram-Nilsson, Kerstin ; Abramo, Livio ; Acero, Alfonso Quijano ; Agger, Poul ; Aleksic, Borislav ; Alexanco, José Luis ; Alviani, Getulio ; Amano, Kazumi ; Amano, Kunihiro ; Amar, Mohamed ; Anderle, Jiri ; Andivero, Antonio ; Antes, Horst ; Asse, Geneviève ; Baias-Lucaci, Ethel ; Balcar, Jiri ; Baldessin, George ; Ball, George ; Ballif, Yannick ; Bates, Martin Pat ; Behrakis, Georges ; Behring, Edith ; Belgeonne, Gabriel ; Ben-Shaoul, David ; Benjamin, Anthony ; Berber, Mersad ; Bergander, Rudolf ; Bergman, Anna-Eva ; Berni, Antonio ; Bernik, Janez ; Bertemes, Roger ; Bhavsar, Natyar ; Böckman, Bengt ; Boljka, Janez ; de Bolle, Francis ; Bompadre, Giorgio ; Boni, Paolo ; Bonnier, Alexandre ; Bonomi, Maria ; Borcic, Bogdan ; Borcic, Vesna ; Borodin, Anatolij ; Borovsky, Borivoj ; Brauer, Erich ; Bravo, Alfredo Sosa ; Breindel, Margaret ; Breivik, Anne ; Bresciano, Miguel ; Brites, Joao ; Broniek, Zofia ; Brunovsky, Albin ; Buchholz, Wolff ; Cabé, Carlos Alberto ; Calderara, Antonio ; Capogrossi, Giuseppe ; Capozzoli, Glauco ; Caracalos, Eugénie ; Caraceni, Bruno ; Carballo, Aida ; Carmi, Eugenio ; Cattelani, Raul ; Caulfield, Patrick ; Celmare, Vasile ; Charbonneau, Monique ; Cleavin, Barry Vickerman ; Corneille ; Cruz, Jaime ; Csohany, Kalman ; Cvorovic, Slavoljub ; D'Arcangelo, Allan ; Dabova, Zlatka ; Debenjak, Riko ; Debska-Narebska, Barbara ; Decleva, Mario ; Denny, Robyn ; Dobrovic, Juraj ; Drawbridge, John ; Drebusch, Günter ; Droste, Karl Heinz ; Dumouchel, Albert ; Dzmerkovic, Bozidar ; Eilat, Avraham ; Ercilla, Jorge Guillermo Luna ; Evans, Merlyn ; Feller, Eugen ; Feszt, Ladislau ; Fijalkowski, Stanislaw ; Fischer, Jürgen ; Forsberg, Jan ; Fossier, Christian-Jean ; Francis, Sam ; Frenken, Wil ; Friedlaender, Gotthard ; Frohner, Adolf ; etc.
biografie
Frans
boek